Effectiveness of Health Education With Peer Education Method On The Attitude Of Student Bse (Breast Self-Examination) In Senior High School 5 Kediri - Anggraeni, Suci; Anggraeni, Cahyu Novita (Institut Ilmu Kesehatan STRADA Indonesia, 2019)
Background: BSE (Breast Self-Examination) is one of the early detection steps to prevent breast cancer is more effective if done as early as possible when adolescents reach the age of reproduction. Purpose : The purpose of this research is to know the influence of health education with peer education method toward student attitude in do realize in Senior High School 5 Kediri.Methods :The research design in this research is pre experimental design with one group pre test approach - post test design. The Sampel is some female students of class XI in Senior High School 5 Kediri as many as 104 respondents taken with Simple Random Sampling technique. Variable dependent attitude of student, independent variable of health education with peer education method. The instrument used is a questionnaire. The results of analysis using Mc Nemar with ? = 0,05.Result : The result of this research is that most respondents have positive attitude in doing BSE before giving health education as much 65 respondent (62,5%), while most of respondent have positive attitude in doing BSE after giving health education 96 responden (92,3%) . The result of Mc Nemar statistic test is obtained ? value = 0,000 <? = (0,05), which means there is Effect of Health Education with Peer Education Method toward Student Attitudes In Conduct BSE in Senior High School 5 Kediri City.Conclusion : Peer education method has relationship with respondent attitude about BSE because counseling with peer education method about is very important for respondent and expected by giving counseling about BSE will increase knowledge and also ability to do BSE for early detection breast cancer.